Memoirs as a Source of Studying the Battle of Leningrad - V. P. Gridnev (Управленческое консультирование)
In the second part of the article, the memories of participants in the Great Patriotic War, including the battle for the city on the Neva, are analyzed. The authors of the memoirs are the People’s Commissar of the Soviet Navy N.G. Kuznetsov, Marshal of the Soviet Union А.М. Vasilevsky, Marshal of the Soviet Union Bagramyan I.Kh., Chief Marshal of Aviation Novikov AA, Admiral Tributs VF, Colonel-General of Artillery Michalkin MS, Colonel-General of Artillery Korobchenko VS, Providing the population of the city of Leningrad and the front with food, Commissar of Trade of the RSFSR, General Quartermaster Service Pavlov DV In addition, 140 conversations with V. Molotov, former Deputy Chairman of the State Defense Committee, First Deputy Chairman of the Council of People’s Commissars of the USSR, and People’s Commissar for Foreign Affairs of the USSR, recorded by F. Chuyev, are analyzed. Memories of other defenders of Leningrad, as well as the Prime Minister of Great Britain, Winston Churchill, are considered.